Ultrasound-induced cavitation renders prostate cancer cells susceptible to hyperthermia: Analysis of potential cellular and molecular mechanisms - Hu, Shaonan; Zhang, Xinrui; Melzer, Andreas; Landgraf, Lisa (Frontiers in Genetics, 2023)
Background: Focused ultrasound (FUS) has become an important non-invasive therapy for prostate tumor ablation via thermal effects in the clinic. The cavitation effect induced by FUS is applied for histotripsy, support drug delivery, and the induction of blood vessel destruction for cancer therapy. Numerous studies report that cavitation-induced sonoporation could provoke multiple anti-proliferative effects on cancer cells. Therefore, cavitation alone or in combination with thermal treatment is of great interest but research in this field is inadequate. Methods: Human prostate cancer cells (LNCap and PC-3) were exposed to 40 s cavitation using a FUS system, followed by water bath hyperthermia (HT). The clonogenic assay, WST-1 assay, and Transwell® invasion assay, respectively, were used to assess cancer cell clonogenic survival, metabolic activity, and invasion potential. Fluorescence microscopy using propidium iodide (PI) as a probe of cell membrane integrity was used to identify sonoporation. The H2A.X assay and Nicoletti test were conducted in the mechanism investigation to detect DNA double-strand breaks (DSBs) and cell cycle arrest. Immunofluorescence microscopy and flow cytometry were performed to determine the distribution and expression of 5α-reductase (SRD5A). Results: Short FUS shots with cavitation (FUS-Cav) in combination with HT resulted in, respectively, a 2.2, 2.3, and 2.8-fold decrease (LNCap) and a 2.0, 1.5, and 1.6-fold decrease (PC-3) in the clonogenic survival, cell invasiveness and metabolic activity of prostate cancer cells when compared to HT alone. FUS-Cav immediately induced sonoporation in 61.7% of LNCap cells, and the combination treatment led to a 1.4 (LNCap) and 1.6-fold (PC-3) increase in the number of DSBs compared to HT alone. Meanwhile, the combination therapy resulted in 26.68% of LNCap and 31.70% of PC-3 with cell cycle arrest in the Sub-G1 phase and 35.37% of PC-3 with cell cycle arrest in the G2/M phase. Additionally, the treatment of FUS-Cav combined with HT block the androgen receptor (AR) signal pathway by reducing the relative Type I 5α-reductase (SRD5A1) level to 38.28 ± 3.76% in LNCap cells, and decreasing the relative Type III 5α-reductase 3 (SRD5A3) level to 22.87 ± 4.88% in PC-3 cells, in contrast, the relative SRD5A level in untreated groups was set to 100%. Conclusion: FUS-induced cavitation increases the effects of HT by interrupting cancer cell membranes, inducing the DSBs and cell cycle arrest, and blocking the AR signal pathway of the prostate cancer cells, with the potential to be a promising adjuvant therapy in prostate cancer treatment.